2015
DOI: 10.1039/c5cc01287b
|View full text |Cite
|
Sign up to set email alerts
|

Cu-catalyzed oxidative Povarov reactions between N-alkyl N-methylanilines and saturated oxa- and thiacycles

Abstract: Cu-catalyzed oxidative Povarov reactions between N,N-dialkylanilines and saturated oxa- or thiacycles with tert-butyl hydroperoxide (TBHP) are described; notably, the reactions use neither [4π] nor [2π]-motifs as the initial reagents. The use of cheap alkane-based substances as building units is of mechanistic and practical interest as two inert sp(3) C-H bonds are activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…However, the desired product 6 can be isolated using basic alumina chromatography. Reductive amination with acetone, mediated by AcOH and NaOAc was also pursued as an alternative strategy [18]. While being much easier to purify due to the elimination of the bis-alkylation product, the yield of this approach was much more variable at larger scales.…”
Section: Resultsmentioning
confidence: 99%
“…However, the desired product 6 can be isolated using basic alumina chromatography. Reductive amination with acetone, mediated by AcOH and NaOAc was also pursued as an alternative strategy [18]. While being much easier to purify due to the elimination of the bis-alkylation product, the yield of this approach was much more variable at larger scales.…”
Section: Resultsmentioning
confidence: 99%
“…In 2018, Lei and co-workers [32] realized the breakthrough of oxidative C(sp 3 )AH phosphonylation of N,Ndialkylaniline derivatives by synergistically combining visible light-induced photoredox catalysis with proton-reduction catalysis (Scheme 2). Note that, this process is performed under external oxidant free conditions and the oxidative breakage of CAN bond side reactions can be successfully avoided [33,34]. Under optimal reaction condition, a variety of N-alkyl substituted anilines, such as N,N-dialkylanilines, cyclic amines can be phosphonylated in good to high yields.…”
Section: Visible Light-mediated C(sp 3 )P Bond Formation Reactionsmentioning
confidence: 99%
“…Liu and co-workersm ade significant progress on the development of oxidative Povarov reactions (Scheme 2). [14] In this new approach, they found that the double oxidationoft ertiary amines 4 and tetrahydrofuran derivatives 5 was feasible under the same catalysis system. In the presence of ac atalytic amount of Cu powder or Cu(OTf) 2 ,t he cycloaddition reactions between N-methyl anilinesa nd saturated oxa-or thiacycles, such as tetrahydrofuran, tetrahydrothiophene, tetrahydro-2Hpyran, and tetrahydro-2H-thiopyran, proceeded smoothly to afford ad iversearray of N-heterocycles 6.…”
Section: Oxidative Iminium Approachmentioning
confidence: 97%
“…Liu and co‐workers made significant progress on the development of oxidative Povarov reactions (Scheme ) . In this new approach, they found that the double oxidation of tertiary amines 4 and tetrahydrofuran derivatives 5 was feasible under the same catalysis system.…”
Section: Oxidative Iminium Approachmentioning
confidence: 99%